Vídeo game como mídia da construção narrativa - Stateri, Julia (2009)
This work has as study object the videogames and it s propose as a narrative creation media. Intends to define the concepts of narrative and game departing from a historical and contextual fundamentation. Through this, intends to align the technological revolution with the creation and evolution of the videogames, considering its social and philosofical implications about individual subjectivity and his possibilities of expression.